2022
DOI: 10.5009/gnl210417
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis Is Associated with an Increased Risk of Colorectal Adenoma and High-Risk Adenoma: A Retrospective, Multicenter, Cross-Sectional, Case-Control Study

Abstract: Background/Aims: The protective effects of vitamin D and calcium on colorectal neoplasms are known. Bone mineral density (BMD) may be a reliable biomarker that reflects the long-term anticancer effect of vitamin D and calcium. This study aimed to evaluate the association between BMD and colorectal adenomas including high-risk adenoma.Methods: A multicenter, cross-sectional, case-control study was conducted among participants with average risk of colorectal cancer who underwent BMD and screening colonoscopy bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A multicenter study in Korea confirmed that osteoporosis is an independent risk factor for colorectal and high-risk adenomas. However, in the subgroup analysis according to sex, osteoporosis increased the risk of adenoma only in women (OR = 1.66, p = 0.034 vs. OR = 1.45, p = 0.417), which is believed to be due to the limited sample size [ 12 ]. Our study targeted a larger sample size and found that osteoporosis increased the risk of CRN regardless of sex, although the OR for this risk was higher in women than in men (OR = 2.06 vs. OR = 1.66, both p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A multicenter study in Korea confirmed that osteoporosis is an independent risk factor for colorectal and high-risk adenomas. However, in the subgroup analysis according to sex, osteoporosis increased the risk of adenoma only in women (OR = 1.66, p = 0.034 vs. OR = 1.45, p = 0.417), which is believed to be due to the limited sample size [ 12 ]. Our study targeted a larger sample size and found that osteoporosis increased the risk of CRN regardless of sex, although the OR for this risk was higher in women than in men (OR = 2.06 vs. OR = 1.66, both p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies have suggested that lower BMD is associated with an increased risk for colorectal adenoma/cancer, especially in postmenopausal women [ 9 , 11 , 12 ]. The biological mechanisms linking bone mass to the risk of CRC are not fully understood; however, cumulative exposure to estrogen may play a role, and so may vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxaliplatin induces kidney failure caused by proximal tubule injury, resulting in hypomagnesaemia, which aggravates bone loss by preventing vitamin D synthesis [24]. In addition, vitamin D has been reported to suppress the growth of malignancies including colorectal cancer [25,26]. Vitamin D deficiency, which reduces BMD, may be one of the causes of poor prognosis in patients with OVF.…”
Section: Discussionmentioning
confidence: 99%